Multiple evidence for methylotrophic methanogenesis as the dominant methanogenic pathway in hypersaline sediments from the Orca Basin, Gulf of Mexico - Zhuang, G.-C.; Elling, F.J.; Nigro, L.M.; Samarkin, V.; Joye, S.B.; Teske, A.; Hinrichs, K.-U. (Elsevier Ltd, 2016)
Among the most extreme habitats on Earth, dark, deep, anoxic brines host unique microbial ecosystems that remain largely unexplored. As the terminal step of anaerobic degradation of organic matter, methanogenesis is a potentially significant but poorly constrained process in deep-sea hypersaline environments. We combined biogeochemical and phylogenetic analyses with incubation experiments to unravel the origin of methane in the hypersaline sediments of Orca Basin in the northern Gulf of Mexico. Substantial concentrations of methane, up to 3.4 mM, coexisted with high concentrations of sulfate from 16 to 43 mM in two sediment cores retrieved from the northern and southern parts of Orca Basin. The strong depletion of 13C in methane (-77‰ to -89‰) points towards a biological source. While low concentrations of competitive substrates limited the significance of hydrogenotrophic and acetoclastic methanogenesis, the presence of non-competitive methylated substrates (methanol, trimethylamine, dimethyl sulfide, dimethylsulfoniopropionate) supported the potential for methane generation through methylotrophic methanogenesis. Thermodynamic calculations demonstrated that hydrogenotrophic and acetoclastic methanogenesis were unlikely to occur under in situ conditions, while methylotrophic methanogenesis from a variety of substrates was highly favorable. Likewise, carbon isotope relationships between methylated substrates and methane suggested methylotrophic methanogenesis was the major source of methane. Stable and radio-isotope tracer experiments with 13C-labeled bicarbonate, acetate and methanol and 14C-labeled methylamine indicated that methylotrophic methanogenesis was the predominant methanogenic pathway. Based on 16S rRNA gene sequences, halophilic methylotrophic methanogens related to the genus Methanohalophilus dominated the benthic archaeal community in the northern basin and also occurred in the southern basin. High abundances of methanogen lipid biomarkers such as intact polar and polyunsaturated hydroxyarchaeols ...